(3fJGFL CacGQ GdKbGJ ajeG ddUaGJ ef GdJYdjbGJs - (3MSjf GdYOhis ((3eMeO GHf GdMGL MSjf HdbGSe s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfGQg HCfhGQg GdeQGOg eUGHjM GdYbhd s
(3BNQgG (B:s
(3ehSi hEHQGgje deG SdeG ef GdEZQGb hGdEMQGb JeJ GdQSGdI HMeO Gddg hMSf Yhfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(105 d) s
Keywords: (3GdJhMjO hGdedd hGdfMds